(3Yjf GdCOH hGdSjGSI hRjf GdMSH hGdQjGSIs - (3Ydj Hf YHO GdQMef Hf gPjd GdaRGQj GdCfOdSj,J (B763 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj hgH dfG GdYbhd hGdCPgGf, hefMfG aUGMI GddSGf hMVfG Ydi GdJMdj HGdMdi hGdJNdb HGdecGQe GdYdjI s
(3BNQgG (B:s
(3hgPG eG cJHg ade GdGSJYLGd, Ydi Vjb GdeLGd GfJgi GdcJGH GdeSei s
(3bOeg GdeDda Edi GdSdWGf eMeO jhSa GdfUQj SfI (B763 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B121s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B131 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B58 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs